2021
DOI: 10.1186/s12862-021-01911-9
|View full text |Cite
|
Sign up to set email alerts
|

European agroforestry has no unequivocal effect on biodiversity: a time-cumulative meta-analysis

Abstract: Background Agroforestry is a production system combining trees with crops or livestock. It has the potential to increase biodiversity in relation to single-use systems, such as pastures or cropland, by providing a higher habitat heterogeneity. In a literature review and subsequent meta-analysis, we investigated the relationship between biodiversity and agroforestry and critically appraised the underlying evidence of the results. Results Overall, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 86 publications
(62 reference statements)
0
19
0
1
Order By: Relevance
“…In our recent meta-analysis [ 1 ], we have shown that agroforestry has no overall positive effect on biodiversity, but we found an effect of small magnitude comparing agroforestry with cropland. In a comment, Boinot et al [ 2 ] raised concerns about our definitions of agroforestry and biodiversity, the selection of the control sites used in our meta-analysis and the applicability of our results for conservation.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In our recent meta-analysis [ 1 ], we have shown that agroforestry has no overall positive effect on biodiversity, but we found an effect of small magnitude comparing agroforestry with cropland. In a comment, Boinot et al [ 2 ] raised concerns about our definitions of agroforestry and biodiversity, the selection of the control sites used in our meta-analysis and the applicability of our results for conservation.…”
mentioning
confidence: 56%
“…Indeed, we have included studies for which control locations were close to the treatment sites and this may potentially underestimate the effect of agroforestry on biodiversity. We have tested whether this was the case by excluding the sites that Boinot et al regard as inappropriate [for code and data see Additional file 1 and 2 ]. The conclusion from the meta-analysis did not change after discarding the case-control comparisons criticized (Fig.…”
Section: Control Site Selectionmentioning
confidence: 99%
“…Despite the strong enthusiasm of the agroforestry research community, a recent systematic review of agroforestry experiments in the Global South concludes that rigorous evidence on the effects of agroforestry on agricultural productivity, ecosystem services, and human well-being remains extremely limited [ 63 ]. Similarly, through their meta-analysis, Mupepele et al [ 1 ] point out that we should not take for granted the positive effects of agroforestry on biodiversity. We add that we should not prematurely underestimate the potential of agroforestry either.…”
Section: Discussionmentioning
confidence: 99%
“…We carefully read the protocols of studies comparing agroforestry systems with arable crops or open pastures, as our primary interest is the benefit of agroforestry systems in agricultural landscapes. We found that at least 11 out of 28 studies included in the meta-analysis by Mupepele et al [ 1 ] did not have adequate control sites. Many studies were designed to assess the distribution of taxa within agroforestry systems [ 7 11 ], not to assess the effect of agroforestry relative to other cropping systems.…”
Section: Inadequate Controls To Assess the Effects Of Agroforestry Sy...mentioning
confidence: 93%
See 1 more Smart Citation